Stink and the shark sleepover - McDonald, Megan; Reynolds, Peter, 1961- (Somerville, MA : Candlewick Press, 2014)
When Stink's parents win an aquarium sleepover, he and his two friends enjoy a scavenger hunt before trying to fall asleep while worrying about the frankensquid on the loose.
Keywords: Public aquariums -- Fiction; Treasure hunt (Game) -- Fiction; Squids -- Fiction